Advancing Lithium- and Manganese-Rich Cathodes through a Combined Electrolyte Additive/Surface Treatment Strategy. Issue 16 (22nd November 2019) - Gutierrez, Arturo; He, Meinan; Yonemoto, Bryan T.; Yang, Zhenzhen; Wang, Jie; Meyer, Harry M.; Thackeray, Michael M.; Croy, Jason R.
Abstract : Lithium- and manganese-rich (LMR) materials provide cost and environmental advantages to other competing cathodes based on nickel or cobalt chemistries. Within the LMR family, layered-layered-spinel (LLS) cathodes have unique properties, detailed herein, that address several of the challenges faced in large-scale implementation of LMR cathodes. This paper details how a LLS//graphite system was considerably improved by combining optimization strategies. First, a cathode surface-treatment process was optimized. Interestingly, cathodes surface-treated at a low temperature (∼100°C) exhibited the best results. The optimized LLS cathode was tested vs. graphite using small amounts of lithium difluoro(oxalate)borate electrolyte additive. The combined approach improved various aspects of the electrochemical performance (e.g., impedance, cycle life, and coulombic efficiency) more than each strategy used alone by mitigating Mn dissolution from the cathode and the ensuing deposition on the anode. The report describes a unique method to improve the performance of practically relevant LMR//graphite cells.